Analysis of an encapsulated phase change material‐based energy storage system for high‐temperature applications. (12th March 2018) - Solomon, Laura; Zheng, Ying; Tuzla, Kemal; Neti, Sudhakar; Oztekin, Alparslan
Summary: The capability of an encapsulated phase change material (EPCM)‐based thermal energy storage (TES) system to store a large fraction of latent energy at high temperatures was examined. A 3‐dimensional simulation of a prototype heat exchanger was conducted employing sodium nitrate as the phase change material (PCM). The k ‐ ω SST model was used to capture the turbulent flow of the HTF, while the melting front was tracked using the enthalpy‐porosity method. The results show that the use of metal deflectors yields a nearly constant heat transfer coefficient over the capsule's surface. Despite this, the presence of the void in the capsule and natural convection within the molten PCM influenced the storage characteristics of the system affecting the shape of the isotherms and melting front. Furthermore, the EPCM capsules consecutively undergo the same heat transfer starting from the capsule closest to the inlet. The EPCM capsules store 80% of the energy lost by the HTF. The 17.7 kg of sodium nitrate stores 14.5 MJ of energy where 20% of the energy stored is via latent heat. Of the energy released by the heat transfer fluid, 80% was absorbed by the EPCM capsules with the remaining energy going into the test section walls. A total of 14.5 MJ of energy was stored by the 17.7 kg of NaNO3, of which 20% is attributed to the latent heat. The fraction of energy stored as latent heat would be larger if a smaller operating temperature range was used. Thus, an EPCM‐based latent heat TES system is capable of storing a large fraction of the supplied energy and presents efficient means of storing thermal energy for high‐temperature applications. Additionally, the strong agreement between the numerical and experimental works demonstrates that the numerical methods employed can predict the behavior of an EPCM capsule not only within a single capsule but on the system scale as well. Therefore, the applied numerical methods can be used for further design and optimization of EPCM‐based latent heat TES systems. Abstract : Three‐dimensional simulations of a pilot‐scale EPCM‐based TES system were conducted. The internal void space and natural convection within the molten PCM influenced the storage characteristics. Eighty percent of the supplied energy was stored in the capsules of which 20% is attributed to the latent heat storage. Strong agreement between the numerical and experimental works demonstrates that the methods employed can predict the behavior an EPCM‐based system, and therefore it can be used to further design and optimize EPCM‐based latent heat TES systems.